Optimasi Aplikasi Pelapisan Nanopartikel Seng Oksida pada Kain Katun-Indigo dengan Response Surface Methodology - Renung Reningtyas; Edia Rahayuningsih; Yuni Kusumastuti; Indriana Kartini (Eksergi, 2023)
The use of nanomaterial as a finishing agent in the textile industry continues to be developed. Nanoparticle zinc oxide (ZnONP) has anti-UV properties so that it can be used to protect the color of the fabric from fading. Constraints of using nanomaterial as a functionalization agent on fabric are the process of application and also its poor adhesion. This research aims to optimize ZnONP coating on cotton-indigo fabric so that ZnONP can be maximized adsorbed with good durability. Optimization is carried out by the Response Surface Methodology (RSM) method, with the independent variables are: ZnoNP Dispersion volume, the number of coating, and the method of coating (with and without sonication assisted). The response variable is the adsorbed ZnONP in fabric sample after the washing process. The number of coating and sonication-assisted coating gives significant results in increasing the number of adsorbed ZnONP.